Examining the Contributions of School Contexts to Teacher Self-regulation among Turkish Teachers: A Structural Equation Modelling Approach - Ulubey, Özgür; Alpaslan, Muhammet Mustafa (Anales de Psicología / Annals of Psychology, 2026)
Self-regulation holds significant importance in the fields of education, business and psychology because it relates individuals to monitor and regulate their knowledge and practice, and eventually self-development and work engagement. Considering Social Cognitive theory, the purpose of this study was to examine the interplay among social contextual variables and teacher self-regulation in Turkey. Data from 314 middle school teachers from forty-five school in Turkey were collected through Teacher Self-regulation Scale (TSRS) and the School Contextual Scale. Structural equation modelling approach was utilized to address research questions. Analysis showed that social contextual variables accounted for 41.4% of the variance in teacher self-regulation. Relations with colleague strongly predicted belonging and value consonance, which was the strongest predictor of teacher self-regulation. Moreover, analyses revealed that relations with colleagues and supervisory support had a statistically significant indirect effect on teacher self-regulation through value consonance. The result of this study implies that when a teacher’s beliefs, norms and values are aligned with those the school has, she is more willing to monitor, control and regulate her teaching practice.